Gender biases in assistant professor recruitment: Does discipline matter? - Heike Solga; Alessandra Rusconi; Sophie Hofmeister (Research Policy, 2025)
Higher education institutions have implemented various affirmative action policies aimed at increasing the representation of female professors, including measures to reduce gender bias in professorship appointments. This raises the question of whether gender bias still exists. Research on gender bias in assistant professor appointments remains sparse. We therefore examine whether gender bias in assistant professor recruitment exists and differs across disciplines (looking at mathematics/physics, economics/sociology/political science, and German studies). Our analysis is based on a factorial survey experiment with 1857 professors from German universities in 2020. We draw on Crandall and Eshleman's (2003) justification-suppression model to argue that gender policies can help suppress the expression of prejudices (negative stereotypes) against female applicants. Our results show that in all disciplines studied, female applicants receive higher ratings than male applicants, both for perceived qualification for an assistant professorship and for being invited for an interview. The female advantage is more pronounced in mathematics/physics when applicants are perceived to be equally qualified, suggesting a greater normative pressure to comply with gender-based preferential selection. In mathematics/physics, however, we also find a smaller premium for having received a research grant among female applicants. Overall, the observed female advantage is rather small in all disciplines studied.
https://doi.org/10.7802/2742
Keywords: 330; Gender bias; Assistant professorships; Disciplinary comparison; Prejudice expression model; German academia